Deficit why should I care? - Bussing-Burks, Marie; SpringerLink (Online service). (Berkeley, CA Apress, 2011)
At the turn of this century, the American national debt stood at just under
Electronic reproduction.
Keywords: Debts, Public -- United States; Budget deficits -- United States; Deficit financing -- United States; Government spending policy -- United States; Fiscal policy -- United States; Electronic books